Аттична чорнолакова керамiка з Ольвiї в зiбраннi Археологiчного музею IА НАН України - Чечуліна, І.О. (Археологія, 2020)
Аттична чорнолакова кераміка — надійне джерело датування археологічних комплексів та культурних нашарувань Ольвії. Колекція кераміки, що експонується в Археологічному музеї Інституту археології НАНУ, — доволі інформативна та цікава з точки зору різноманітності форм та орнаментування. В експозиції представлені як окремі речі, так і цілі комплекси посуду різного часу, переважно класичного та елліністичного. Чернолаковая керамика занимает особое место среди многочисленных категорий импорта из Аттики в Северное Причерноморье. В Археологическом музее НАН Украины находится довольно многочисленная и репрезентативная коллекция античных древностей, найденных в Ольвии. Предметом исследования является аттическая чернолаковая керамика, которая была найдена в Ольвии в разные годы экспедицией ИА НАН Украины (1962— 2000 гг.). В статье рассмотрены шестнадцать целых сосудов из экспозиции музея. Подавляющее большинство составляют сосуды для питья вина, которые датируются главным образом в пределах 500—325 гг. до н. э. Это, в частности, чаши типа «болсал» — два экземпляра; канфароподобный килик, два канфара эллинистического времени с накладным орнаментом, канфар классической формы с каннелюрами и один канфар — микроформа; скифосоподобный килик, чаша на высокой ножке, килик типа «delicate class» и килик на ножке («vicup»). Отдельную группу столовой посуды составляют миски и блюда. Это миска с отогнутым наружу краем, рыбное блюдо и солонка. К редким находкам посуды закрытых форм относится ойнохоя с рельефным орнаментом V в. до н. э. Приведенные формы принадлежат к парадной столовой посуде и еще раз демонстрируют активные торговые отношения Ольвийского полиса с Аттикой в течении классического и эллинистического времени. Наличие большого количества аналогий с античных памятников Причерноморского региона, в частности городов Боспора, Херсонеса, Тиры, Истрии, Аполлонии, некрополей и поселенческих памятников их сельских округ доказывает, что импорт аттической керамики в Ольвию был частью большой торговой экспансии с Аттики к государствам Понта Эвксинского в V—IV вв. до н. э. Ольвия была стратегическим пунктом на основном торговом пути в города и поселения Северного Причерноморья, проходившего вдоль западного побережья. Именно поэтому, среди находок городища, хоры и некрополей города встречаются почти все категории этого вида посуды. Коллекция материалов из Ольвии является эталонной для других городов Северного Причерноморья и именно поэтому требует всестороннего анализа и тщательного внимания. Amount of Attic tableware and ceremonial ware finds in the Northern Black Sea region is large, and that is why they are so important since they provide information for detailed chronology of ancient material. 82 ISSN 0235-3490 (Print), ISSN 2616-499X (Online). Археологія, 2020, № 2 The collection of finds from Olbia, which is exhibited in the Archaeological Museum of the IA NASU is quite numerous. The investigated part of the material includes Attic black-glazed pottery, which was found in Olbia in different years at various sites of excavations, from 1962 to 2000. The vast majority of the studied collection consists of vessels for drinking wine — eleven vessels of sixteen studied, dating by the Athenian Agora from 500 to 325 BC. Pottery for wine are represented by cups and kantharoi in varioustypes. These are the cup — «bolsal» — two examples; cup-kantharos — two examples; one Hellenistic kantharos with an applique ornament and one kantharos — microform; cup-skyphos; stemmed dish; cup «delicate class» and a stemmed cup («vicup»). «Opened» types of pottery include a bowl with an outturned rim 350—325 BC and a fish plate 350—325 BC, a saltcellar from the same time of production. Rare finds of «closed» pottery forms are oinohoe with a relief ornament of V century BC. All the forms above have direct analogies in the material from the Athenian Agora and finds of Attic black-glazed ware from other cities of the Northern Black Sea. These forms belong to the ceremonial tableware and demonstrate an active trade relation of Olbia with the Attic region during the Classical and Hellenistic time. The abundance of analogies from the ancient sites of the Black Sea region, including the cities of the Bosporus, as well as Chersonesos, Tyras, Histria, Apollonia, necropolises and settlements of their rural districts, proves that the import of Attic ceramics to Olbia was a part of a large trade expansion from Attica to the cities of Pont Euxine in V—IV centuries BC. Trade relation were systematic, developing consistently, covering more and more ancient cities of the Black Sea region and beyond. Olbia was a strategic point on the main trade route to other cities and settlements along the western coast, across Olbia. For this reason, almost all categories of this type of tableware are among the finds of the settlement and necropolises of the city. Olbia’s collection of materials is a benchmark for other Northern Black Sea cities, which is why it needs thorough analysis and careful attention.